Graphene heat-conducting film reinforced copper-based three-dimensional heat-conducting composite material and preparation method

CN122956792APending Publication Date: 2026-10-23陕西香云企业管理有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611373698.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明为解决现存的技术问题而提供一种石墨烯导热膜增强铜基三维导热复合材料及制备方法,解决了传统多层石墨烯叠层因层间结合力弱、法向导热极差而无法作为厚尺寸块材使用的技术难题

Benefits of technology

[0015]本发明提供的一种石墨烯导热膜增强铜基三维导热复合材料及制备方法,相比现有技术,本方法取得的效果有:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956792A_ABST
    Figure CN122956792A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of heat-conducting materials, and discloses a graphene heat-conducting film reinforced copper-based three-dimensional heat-conducting composite material and a preparation method thereof, which comprises horizontally stacked multilayer graphene heat-conducting films; high-heat-conducting carbon fibers which penetrate through all the film layers in a direction perpendicular to the plane of the graphene heat-conducting films, forming vertical heat-conducting channels; and filling copper which is densely filled in the interlayer gaps of the graphene heat-conducting films, the gaps between the high-heat-conducting carbon fibers and the film hole walls and residual pores; wherein the graphene heat-conducting films, the high-heat-conducting carbon fibers and the filling copper jointly constitute a three-dimensional continuous heat-conducting network. The application adopts a textile type carbon fiber sewing process, introduces the high-heat-conducting carbon fibers into the graphene film stack in a vertical sewing mode, forms a three-dimensional skeleton preform with continuous vertical heat-conducting channels, and fundamentally solves the technical problem that traditional multilayer graphene stacks cannot be used as thick-size blocks due to weak interlayer bonding force and poor normal heat conduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal conductive materials technology, and in particular to a graphene thermal conductive film-reinforced copper-based three-dimensional thermal conductive composite material and its preparation method. Background Technology

[0002] With advancements in integrated circuit manufacturing processes, the heat flux density of high-power electronic chips (such as CPUs, GPUs, and AI accelerator chips) has increased dramatically, leading to increasingly severe localized hotspot problems. While traditional pure copper heat sinks have a relatively high thermal conductivity (approximately...),... However, it gradually became unable to meet the high-efficiency heat conduction requirements of high-power electronic chips.

[0003] Graphene thermal conductive films have extremely high in-plane thermal conductivity (up to 100%). The above (referring to graphene films) makes them ideal heat homogenizers. However, the thickness of a single graphene film is extremely small, and when multiple layers are stacked, the normal thermal conductivity between the layers is extremely low (typically only a few times the normal thermal conductivity). This creates a significant vertical thermal resistance bottleneck, making it impossible to directly use pure graphene film stacks as thick heat dissipation blocks.

[0004] Existing technologies have attempted to combine graphene with copper, such as through ball milling and powder sintering, or electrodeposition and co-deposition. However, in these composite materials, the graphene is often randomly dispersed or planarly oriented, making it difficult to construct a continuous vertical thermal conductivity pathway spanning the entire thickness of the material. Furthermore, the poor interfacial wettability between graphene and the copper matrix results in high interfacial thermal resistance, limiting the overall improvement in the thermal conductivity of the composite material. More importantly, existing technologies have not solved the problem of how to introduce a continuous, high-proportion, high-thermal-conductivity reinforcing phase in the vertical direction. Summary of the Invention

[0005] This invention provides a graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material and its preparation method to solve existing technical problems. It solves the technical problem that traditional multilayer graphene stacks cannot be used as thick-sized bulk materials due to weak interlayer bonding and extremely poor normal thermal conductivity.

[0006] To solve the above-mentioned technical problems, according to one aspect of the present invention, more specifically, a graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material, comprising: Horizontally stacked multilayer graphene thermal conductive film; High thermal conductivity carbon fibers penetrate the entire film layer in a direction perpendicular to the plane of the graphene thermal conductive film, forming a vertical thermal conductive channel; Copper is filled densely into the interlayer gaps of the graphene thermally conductive film, the gaps between the highly thermally conductive carbon fibers and the film pore walls, and the residual pores. The graphene thermal conductive film, the high thermal conductivity carbon fiber, and the copper filler together form a three-dimensional continuous thermal conductive network.

[0007] Furthermore, the in-plane thermal conductivity of the graphene thermal conductive film... The thickness of a single-layer graphene thermal conductive film is The axial thermal conductivity of the high thermal conductivity carbon fiber The diameter of the single filament of the high thermal conductivity carbon fiber is .

[0008] Furthermore, the volume percentage of the graphene thermal conductive film is... The volume percentage of the high thermal conductivity carbon fiber is The volume percentage of the filler copper is .

[0009] Furthermore, the total thermal resistance of the graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material is reduced by at least [percentage missing] compared to pure copper of the same size. Density less than that of pure copper .

[0010] A method for preparing a graphene-reinforced copper-based three-dimensional thermally conductive composite material, specifically comprising: Step S1: Lay out and stack the multilayer graphene thermal conductive film, and use high thermal conductivity carbon fiber to vertically puncture and sew all the film layers to form a three-dimensional skeleton preform. Step S2: Fill all gaps in the three-dimensional skeleton preform with copper filler. Step S3: Place the filled composite material in a vacuum or inert gas atmosphere and perform hot pressing densification treatment to cause creep in the filled copper matrix and achieve interfacial diffusion bonding. Step S4: Grind or polish the hot-pressed and densified composite material to the preset thickness and surface roughness, and perform anti-oxidation treatment on the surface.

[0011] Furthermore, in step S1, the sewing is performed using a CNC sewing machine according to a preset array pattern, the hole spacing of which is determined based on the volume ratio of the target carbon fiber.

[0012] Furthermore, in step S2, the filler copper is filled using a pulse electroplating process, specifically: Step 1: Use the three-dimensional skeleton prefabricated body as the cathode; Step 2: Electroplating is performed in an acidic copper plating solution; Step 3: Control the filling copper to grow outward from the surface of the internal pores.

[0013] Furthermore, in step S2, the copper filler is applied using a vacuum pressure impregnation process, specifically as follows: Step 1: Place the three-dimensional skeleton preform in a vacuum pressure impregnation furnace; Step 2: Evacuate the vacuum pressure impregnation furnace to a vacuum level and fill it with inert gas until... ; Step 3: Immerse the three-dimensional skeleton preform into... The impregnation is completed by holding the liquid under pressure in molten oxygen-free copper for 15-30 minutes.

[0014] Furthermore, in step S3, the temperature for hot pressing densification is... The pressure is The heat preservation and pressure holding time is 30-60 minutes.

[0015] This invention provides a graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material and its preparation method. Compared with the prior art, the advantages achieved by this method are: 1. This invention employs a textile-style carbon fiber stitching process to introduce highly thermally conductive carbon fibers into graphene film stacks via vertical stitching, forming a three-dimensional skeleton prefabricated structure with continuous vertical thermal conductivity pathways. This process naturally ensures the precise vertical orientation of the carbon fibers and the precise positioning of the graphene film layers, fundamentally solving the technical problem that traditional multilayer graphene stacks cannot be used as thick-sized bulk materials due to weak interlayer bonding and extremely poor normal thermal conductivity. Simultaneously, it avoids the defects of disordered graphene dispersion and the inability to construct continuous vertical thermal conductivity pathways in existing ball milling or electrodeposition methods.

[0016] 2. This invention constructs a three-dimensional continuous thermally conductive network through the synergistic effect of vertically threaded carbon fibers and densely filled copper. Vertically, the carbon fiber bundles and dense copper phase together form an array of "thermal vias" penetrating the material thickness, providing vertical thermal conductivity far exceeding that of pure copper. Horizontally, the graphene film provides ultra-high in-plane thermal conductivity, achieving excellent heat uniformity. During vacuum hot pressing, the copper substrate undergoes creep and forms atomic-level mechanical interlocking and diffusion bonding at the interfaces, completely eliminating interfacial thermal resistance between graphene and copper, between carbon fibers and copper, and between each film layer, enabling unimpeded high-speed heat transfer in all three dimensions.

[0017] 3. This invention utilizes pulsed electroplating copper filling combined with vacuum hot pressing for densification, with the highest process temperature throughout being far below the melting point of copper. This low-temperature process fully preserves the inherent ultra-high thermal conductivity of both the graphene thermal conductive film and the carbon fiber, avoiding damage to the structural integrity of the carbon material caused by high-temperature treatment. Simultaneously, it achieves atomic-level gap filling and interfacial bonding, ensuring optimal overall thermal conductivity of the composite material.

[0018] 4. This invention allows for flexible adjustment of the volume ratio of carbon fiber and copper by modifying the density, pattern, and copper filling amount of the stitching array. This enables precise design of the composite material's vertical thermal conductivity, horizontal thermal conductivity, and total thermal resistance, achieving on-demand customization of thermal performance. For the heat dissipation requirements of different power chips, gradient thermal conduction structures or materials with anisotropic thermal conductivity ratios can be designed, offering strong design flexibility and application adaptability. Attached Figure Description

[0019] Figure 1 This is a three-dimensional structural diagram of the present invention; Figure 2 This is a process flow diagram of Embodiment 1 of the present invention; Figure 3 This is a process flow diagram of Embodiment 2 of the present invention. Detailed Implementation

[0020] To make the technical solution of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0021] Example 1

[0022] This embodiment prepares a copper-based three-dimensional thermally conductive composite material reinforced with carbon fiber stitched graphene thermally conductive film according to the route of "pulse electroplating copper filling + vacuum hot pressing densification". The specific steps are as follows: Step 1: Stitching graphene film laminations with carbon fiber Select an in-plane thermal conductivity of Single layer thickness is High thermal conductivity graphene film (or artificial graphite thermal conductive film treated with high temperature graphitization) is cut into the following shapes. A square sheet. An axial thermal conductivity coefficient of [value missing] is selected. The diameter of the single filament is Pitch-based carbon fiber filaments (or graphene thermal conductive film cut into thin strips as interlayer thermal conductive seams).

[0023] Graphene films were stacked layer by layer until the total thickness was approximately (Approximately 44 layers), secured on all four sides with precision clamps. Place the clamps on the CNC sewing machine's worktable, and set the needle spacing to [value missing]. A square array. Carbon fibers are threaded through a needle, vertically piercing all membrane layers according to a pre-set program to complete the stitching and form a three-dimensional skeleton prefabrication. For thicker graphene films stacked layer by layer, laser perforation can be used followed by threading carbon fiber filaments. In this step, the carbon fiber volume ratio is approximately .

[0024] Step 2: Pulse electroplating copper filling The prefabricated body obtained in step one, used as the cathode and a phosphor bronze plate as the anode, is immersed in an acidic copper sulfate plating solution. The plating solution formula is: copper sulfate... ,sulfuric acid Appropriate amounts of commercial gloss and leveling agent.

[0025] Electroplating is performed using a periodically commutating pulse power supply, with a forward current density of... The reverse current density is The cycle is Positive / Reverse. During the electroplating process, supplemented with... Ultrasonic stirring.

[0026] The total electrical charge is precisely controlled using Faraday's law, based on the target copper volume ratio. The total charge is calculated to be approximately 9 minutes for electroplating. This allows the copper layer to grow uniformly epitaxially from the surface of the internal pores, gradually filling the gaps between the graphene film layers, the gaps between the carbon fibers and the film pore walls, and all remaining pores.

[0027] Step 3: Vacuum hot pressing densification After electroplating, the sample was cleaned with deionized water and dried. The electroplated composite material was then placed in a vacuum autoclave and evacuated to a vacuum level. (Vacuum degree is better than) ), heated to , apply The pressure is maintained for 45 minutes to induce creep in the copper matrix and promote interfacial diffusion bonding, thus completely eliminating residual micropores. The copper is then cooled in the furnace.

[0028] Step 4: Post-processing Remove the sheet material obtained in step three, and use a precision surface grinder to grind both the top and bottom surfaces to the final thickness. Surface roughness Ra reaches ( Electroless nickel plating on the surface. Perform anti-oxidation treatment.

[0029] The composite material obtained in this embodiment has a vertical thermal conductivity of [value missing]. The horizontal thermal conductivity is ,exist Size, center The total thermal resistance under heat source conditions is Compared to the total thermal resistance of pure copper under the same conditions ( (reduced by approximately) The density is approximately Its density is only that of pure copper (approximately) )of .

[0030] Example 2

[0031] This embodiment prepares a copper-based three-dimensional thermally conductive composite material reinforced with carbon fiber stitched graphene thermally conductive film using the route of "molten copper vacuum pressure infiltration + hot pressing". The specific steps are as follows: Step 1: Stitching graphene film laminations with carbon fiber Same as step one in Example 1. Select an in-plane thermal conductivity of... Single layer thickness is High thermal conductivity graphene film, cut into... A square sheet. An axial thermal conductivity coefficient of [value missing] is selected. The diameter of the single filament is Pitch-based carbon fiber filaments.

[0032] Graphene films were stacked layer by layer until the total thickness was approximately (Approximately 44 layers), secured on all four sides with precision clamps. Place the clamps on the CNC sewing machine's worktable, and set the needle spacing to [value missing]. A square array. Carbon fibers pass through the needles, vertically piercing all membrane layers according to a preset program, completing the sewing and forming a three-dimensional skeleton prefabricated body.

[0033] Step 2: Vacuum pressure impregnation of molten copper Place the prefabricated body obtained in step one, after sewing, into a vacuum pressure impregnation furnace. First, evacuate the furnace until... Next, high-purity argon gas is introduced until... ( (Within the range). Place oxygen-free copper in a crucible and heat to... ( Within the specified range, the copper is completely melted. The preform is slowly immersed in the molten copper and held under pressure for 20 minutes (within the range of 15-30 minutes) to complete the impregnation, allowing the molten copper to fully fill all the gaps in the preform.

[0034] Step 3: Vacuum hot pressing densification After slow cooling, the casting is removed. The impregnated composite material is then placed in a vacuum autoclave. , Vacuum hot pressing for 45 minutes under certain conditions causes creep in the copper matrix and promotes interfacial diffusion bonding, further eliminating residual micropores.

[0035] Step 4: Post-processing Same as step four in Example 1. Grind the hot-pressed sheet material on both sides using a precision surface grinder to the final thickness. Surface roughness Ra reaches And chemically plated nickel on the surface. Perform anti-oxidation treatment.

[0036] Tests showed that the vertical thermal conductivity of the composite material obtained in this embodiment is approximately [value missing]. ,exist The total thermal resistance at this size is approximately It has a higher total thermal resistance than pure copper under the same conditions.

[0037] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A graphene-reinforced copper-based three-dimensional thermally conductive composite material, characterized in that, include: Horizontally stacked multilayer graphene thermal conductive film; High thermal conductivity carbon fibers penetrate the entire graphene thermal conductive film in a direction perpendicular to the plane of the graphene thermal conductive film, forming a vertical thermal conductive channel. Copper is filled densely into the interlayer gaps of the graphene thermally conductive film, the gaps between the highly thermally conductive carbon fibers and the film pore walls, and the residual pores. The graphene thermal conductive film, the high thermal conductivity carbon fiber, and the copper filler together form a three-dimensional continuous thermal conductive network.

2. The graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material according to claim 1, characterized in that: The in-plane thermal conductivity of the graphene thermal conductive film The thickness of a single-layer graphene thermal conductive film is The axial thermal conductivity of the high thermal conductivity carbon fiber is... The diameter of the single filament of the high thermal conductivity carbon fiber is .

3. The graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material according to claim 1, characterized in that: The volume percentage of the graphene thermal conductive film is The volume percentage of the high thermal conductivity carbon fiber is The volume percentage of the filler copper is .

4. The graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material according to claim 1, characterized in that: The total thermal resistance of the graphene-reinforced copper-based three-dimensional thermally conductive composite material is reduced by at least [amount missing] compared to pure copper of the same size. Density less than that of pure copper .

5. A method for preparing a graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material, characterized in that, The graphene thermally conductive film reinforced copper-based three-dimensional thermally conductive composite material, applicable to any one of claims 1-4, is prepared by a method comprising: Step S1: Lay out and stack the multilayer graphene thermal conductive film, and use high thermal conductivity carbon fiber to vertically puncture and sew all the film layers to form a three-dimensional skeleton preform. Step S2: Fill all gaps in the three-dimensional skeleton preform with copper filler. Step S3: Place the filled composite material in a vacuum or inert gas atmosphere and perform hot pressing densification treatment to cause creep in the filled copper matrix and achieve interfacial diffusion bonding. Step S4: Grind or polish the hot-pressed and densified composite material to the preset thickness and surface roughness, and perform anti-oxidation treatment on the surface.

6. The method for preparing the graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material according to claim 5, characterized in that: In step S1, the sewing is performed using a CNC sewing machine according to a preset array pattern. The hole spacing of the preset array pattern is determined based on the volume ratio of the target carbon fiber.

7. The method for preparing the graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material according to claim 5, characterized in that: In step S2, the filler copper is filled using a pulse electroplating process, specifically as follows: Step 1: Use the three-dimensional skeleton preform as the cathode; Step 2: Electroplating is performed in an acidic copper plating solution; Step 3: Control the filling copper to grow outward from the surface of the internal pores.

8. The method for preparing the graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material according to claim 5, characterized in that: In step S2, the copper filler is applied using a vacuum pressure impregnation process, specifically as follows: Step 1: Place the three-dimensional skeleton preform in a vacuum pressure impregnation furnace; Step 2: Evacuate the vacuum pressure impregnation furnace to a vacuum level and fill it with inert gas until... ; Step 3: Immerse the three-dimensional skeleton preform into... Impregnation is completed by holding the solution under pressure in molten oxygen-free copper liquid for 15-30 minutes.

9. The method for preparing the graphene thermally conductive film-reinforced copper-based three-dimensional thermally conductive composite material according to claim 5, characterized in that: In step S3, the temperature for hot pressing densification is... The pressure is The heat preservation and pressure holding time is 30-60 minutes.